The Correlation between Clean and Healthy Living Behavior and Diarrhea Incidence in Children Under Five Years Old: A Literature Review Study - Dwiana Mei Desti Setyarini; Nur Hidaayah (Jurnal Ilmiah Kesehatan, 2022)
Diarrhea is a disease often accompanied by mortality and morbidity. Its incidenceincreased 1% per year from 300 thousand household samples. Lack of Clean andHealthy Living Behavior (in Indonesia, namely of a program is Perilaku Hidup BersihSehat or PHBS) can affect the incidence of diarrhea. This paper analyzes the correlationbetween PHBS and diarrhea incidence in children under five years old. The four PHBSindicators are exclusive breastfeeding, healthy latrines, clean water, and handwashingwith soap (HWS). This research was a literature review study. We used a database ofgoogle scholar and the garuda portal. In addition, journal screening included threestages. The first stage was the selection of free access journals. Then, the second stagewas the selection of titles and abstracts according to the keywords (PHBS, Diarrhea, andChildren under five years old) and publication year. The third stage was selecting thebackground, method, results, and discussion. Eleven papers explained the correlationbetween the PHBS and diarrhea incidence in children under five. There were fivearticles revealing the association between the incidence of diarrhea and four PBHSindicators. In addition, PHBS indicators most associated with diarrhea sequentially werehandwashing with soap (11 publications), exclusive breastfeeding (10 journals), healthylatrines (8 papers), and clean water (6 documents). In conclusion, exclusivebreastfeeding, clean water, healthy latrines, and handwashing with soap correlate todiarrhea incidence in children under five years old. Health workers should providehealth education regarding PHBS.